Weak Convergence Theorems for Mixed Type Asymptotically Nonexpansive Mappings (Journal of Mathematical Study, 2015)
The purpose of this paper is to prove some weak convergence theorems formixed type asymptotically nonexpansive mappings with mean errors in uniformlyconvex Banach spaces. The results presented in this paper extend the correspondingresults in the references.
Keywords: Mixed type asymptotically nonexpansive mappings; uniformly convex Banach space; common fixed point; weak convergence.